PENGURANGAN POLLUSI RADIASI MEDAN ELEKTROMAGNETIK DENGAN PENEMPATAN KAWAT GROUNDING ANTARA KONDUKTOR PHASA DAN KONTUR PERMUKAAN TANAH - Utama, Budi (ReTII, 2015)
A simulation method for remodification of the arrangement of the element of the Maxwell Potential Coefficient MatrixÂ (MPCM)Â whichÂ hasÂ been adjustedÂ toÂ :Â aÂ configurationÂ modelÂ ofÂ phaseÂ conductorsÂ ofÂ theÂ ultraÂ highÂ voltage transmission line on the tower, andÂ Â their composite model of the ground wires that is separately located under phase conductors, all of them are presented. The purpose of the MPCM element remodification is an implementation of reduction of electric field intensity (EFI) level. The remodification must be based to forming of the design of the geometric dimension of the air gapÂ between â€œthe ground wiresâ€ placed at the bottom of the phase conductors and the surface of the ground.Â Â â€œThe ground wiresâ€ are additional ground wires aside fromÂ the overhead ground wires. The sample is a ultra high voltage transmission lines (1145 kV), 3 phase, 13.5 meters in phase spacing, phase conductor 16.8 meters in height, and horizontal configuration (flat). The additional ground wires placed off the outer phase (at the bottom of the phase conductor) at the point ofÂ maximum gradient and at a height of 7 metersÂ above ground. TheÂ resultÂ ofÂ computationÂ showÂ thatÂ electricÂ fieldÂ intensityÂ levelÂ canÂ beÂ significantlyÂ decreasedÂ 27.4Â % in magnitude. However, the reduction of the electromagnetic field radiation using electrode of the additional ground wires aside from the overhead ground wires will be decrease electric field intensity (EFI) level, specially for ultra high voltage transmission lines, horizontal configuration,Â a 3 phase, 13.5 meters in phase spacing, and phase conductor 16.8 meters in height.